The Influence of the Program “Damai Indonesiaku” on Tvone on Religious Tolerance Among the People of Depok City - Alfan BACHTIAR; Andi Mirza RONDA; Nandang MULYASANTOSA (International Journal of Environmental, Sustainability, and Social Science, 2025)
This research contains information about the broadcast of television programs containing religious messages about tolerance, religious harmony, and religious cultural values has an important role in shaping the congregation behavior. This study uses SOR Theory, Syringe Theory, Cultivation Theory, Da'wah Communication Theory, and Media Effects Theory. The aim of this study is to examine the influence of da'wah strategies on various important variables, namely: da'wah strategies, the acceptance of messages, congregation behavior, level of religiosity, and religious tolerance. This study specifically analyzes: The direct influence of da'wah strategies on religious tolerance, The influence of da'wah strategies on the acceptance of messages, The influence of da'wah strategies on congregation behavior, The influence of da'wah strategies on the level of religiosity, The influence of the acceptance of messages on religious tolerance, The influence of the acceptance of messages on congregation behavior, The influence of the acceptance of messages on the level of religiosity, The influence of congregation behavior on the level of religiosity, The influence of congregation behavior on religious tolerance, The influence of level of religiosity on religious tolerance. This study uses a quantitative approach with a survey method. The data was collected by distributing questionnaires to 100 respondents determined using the Yamane formula. The results of the study show that the da'wah strategy does not directly increase religious tolerance, but can influence the acceptance of messages and the congregation behavior.